Frequência de aglutininas anti Leptospira interrogans em equídeos em Minas Gerais, 2003/04. - Denise Chiareli (2007)
The goal of this research is to find out the frequency and spatial distribution of infection caused by Leptospira interrogans in equidae in Minas Gerais from September 2003 to March 2004. It was analyzed 6475 samples of blood serum using microscopic agglutination test. From the total, 381 samples were positive reagent (5, 88%) with title equal or superior of 1:200 for one or more serovars of leptospira. The most frequent serovars were hardjo (Norma), pomona, bratislava and batavie. The higher frequency of equidae reagents happen at the North and North east portion of Minas Gerais, followed by the area of Minas Gerais called Triângulo Mineiro and Alto Paranaíba, then Central of Minas/West of Minas/Metropolitan area of Belo Horizonte and South/Southwest of Minas. The frequency of serovars changed among the regions. The variable of sex, species, breeds and age didnt show significant statistic difference.